2018
DOI: 10.1177/0098628318779257
|View full text |Cite
|
Sign up to set email alerts
|

Introduction to Psychology

Abstract: A robust literature has explored multiple facets of the introductory psychology course, but few studies have examined its purposes, student learning outcomes (SLOs), and assessment practices. The second iteration of the Undergraduate Study in Psychology gathered data on these facets in a nationally representative sample of associate ( n = 62) and baccalaureate psychology programs ( n = 161). Most department chairs indicated that their intro course served as both an introduction to the major and a general educa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
11
0
4

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 16 publications
(15 citation statements)
references
References 14 publications
0
11
0
4
Order By: Relevance
“…1(1);1-20 (2022) In addition, the enthusiasm of the sports players for the SHC system was very evident when the sports actors submitted their input and criticism of the prototype of the SHC system which they felt was not suitable for their conditions and needs or needed to add features that could be useful for them and help when implemented in the field. Judging from their enthusiasm, it can be said that they feel the benefits and want the benefits to be maximized by providing input for better improvements (Kern et al, 2020;Pfund, Norcross, Hailstorks, Stamm, & Christidis, 2018). For example, they added that the SHC security system needs to be improved, they also want that the SHC system needs to be added with a sports venue location-finding feature to make it easier for people who want to find a sports place or work place for the Trainer they are interested in and also they want validation of the legality file of the Sports Actor who registers in the SHC system so that the Professionalism of Sports Actors is truly convincing and safe for the community.…”
Section: Discussionmentioning
confidence: 99%
“…1(1);1-20 (2022) In addition, the enthusiasm of the sports players for the SHC system was very evident when the sports actors submitted their input and criticism of the prototype of the SHC system which they felt was not suitable for their conditions and needs or needed to add features that could be useful for them and help when implemented in the field. Judging from their enthusiasm, it can be said that they feel the benefits and want the benefits to be maximized by providing input for better improvements (Kern et al, 2020;Pfund, Norcross, Hailstorks, Stamm, & Christidis, 2018). For example, they added that the SHC security system needs to be improved, they also want that the SHC system needs to be added with a sports venue location-finding feature to make it easier for people who want to find a sports place or work place for the Trainer they are interested in and also they want validation of the legality file of the Sports Actor who registers in the SHC system so that the Professionalism of Sports Actors is truly convincing and safe for the community.…”
Section: Discussionmentioning
confidence: 99%
“…A more recent national survey of chairs of psychology departments conducted by the APA Education Directorate found that about a third of departments reported using APA (2013) guidelines in developing student learning objectives for the IP course, either in their entirety or with only minor changes (Pfund et al, 2018). Although the chairperson may be an appropriate point of contact to ascertain goals and objectives of the IP course, a clearer understanding of course content in individual courses may be approached more directly by use of instructor surveys.…”
Section: Analysis Of Topical Coverage In Ip Coursesmentioning
confidence: 99%
“…These kinds of instruments are crucial to provide information of students´ ability to transfer knowledge to real contexts, as well as being more authentic and motivating (Zaim, Refnaldi, & Arsyad, 2020). Nevertheless, more than 70% of undergraduate programs assess leaning through written tests (Gitanjali, 2016;Pfund, Norcross, Hailstorks, Stamm, & Christidis, 2018). These tests, while trying to cover the whole range of learning outcomes, tend to focus on accumulation of International Journal of Instruction, April 2021 • Vol.14, No.2 information, partial understanding of content, and not promote deep approaches to learning (Biggs, & Tang, 2011;Price, Carroll, O´Donovan, & Rust, 2011;Endedijk, & Vermunt, 2013).…”
Section: Introductionmentioning
confidence: 99%